Review on Current Research Status on Bottom Ash: An Indian Prospective - Mandal A.K.; Sinha O.P. (My University, 2025)
India focuses on attention towards “greener and cleaner” environment surrounding us. For that, the engineers and scientists have joined hands together to accept the challenges for recycling wastes from industries. The generation of Bottom Ash (BA) from thermal power plants which are being increased day by day and facing disposal and environmental problems. In spite of that, it is being used as landfills which has no commercial value, but now needs to think on its utilization as useable supplementary materials. But from the literature survey, it was found that a little amount of research have been carried out on BA in the area based on its adsorption capability of dyes; pelletization efficiency of cold bonded aggregate; compressive strength, durability, water absorption characteristics and density variation in concrete and mortar; in order to ensure its usage as adsorption as well as construction material. The present paper deals with a critical review on BA as an adsorbent, light weight aggregate as well as partial replacement of fine aggregate in concrete. In addition, physical and chemical properties, transportation and disposal mechanism and environmental effects are also discussed. © 2014, The Institution of Engineers (India).